Respuesta :

Explanation:

a) K(s) + I2(s)  --> KI(s)

The balanced equation is;

2K(s) + I2(s)  --> 2KI(s)

b) Mg(s)  +  Br2(l)  --> MgBr2(s)

The balanced equation is;

Mg(s)  +  Br2(l)  --> MgBr2(s)

c) KBr(aq)  +  AgNO3(aq)  --> KNO3(aq)  + AgBr(s)

The balanced equation is;

KBr(aq)  +  AgNO3(aq)  --> KNO3(aq)  + AgBr(s)

d) KClO3(s)  --> KCl(s)  +  O2(g)

The balanced equation is;

2KClO3(s)  --> 2KCl(s)  +  3O2(g)

e) C2H6(g)  +  O2(g)  -->  CO2(g)  + H2O(l)

The balanced equation is;

2C2H6(g)  +  7O2(g)  --> 4CO2(g)  + 6H2O(l)

f) Al(s)  +  O2(g)  --> Al2O3(s)

The balanced equation is;

4Al(s)  +  3O2(g)  --> 2Al2O3(s)

g) P4(s)  +  H2(g)  --> PH3(g)

The balanced equation is;

P4(s)  +  6H2(g)  --> 4PH3(g)